Significant effect of concentration ratio in synthesizing titania nanoflowers (TNF) powder via facile hydrothermal method - Azhar, Faiz Hafeez; Harun, Zawati; Yunos, Muhamad Zaini; Ahmad, Azlinorazia; Mohd Akhair, Siti Hajar; Raja Ahmad, Raja Adibah; Abd Rashid, Abdul Qaiyyum; Hussin, Rosniza; Ibrahim, Siti Aida; Ahmad, Mohd Khairul (Penerbit UTM Press, 2018)
The significant effect of titanium butoxide and hydrochloric acid (TBut/HCl) concentration ratio in synthesizing titania nanoflowers (TNF) towards powder morphologies, crystallographic phases, surface area and band gap were investigated. Various synthesized titania nanostructure were prepared via facile hydrothermal method using titanium butoxide and hydrochloric acid as a mixing composition. The morphologies of synthesizing titania powder were analyzed by using FE-SEM to observe the shape and geometry of the synthesized powder. XRD was used to determine the crystallographic phases of synthesized powder at 2θ angles of 25° to 75°. Each sample was then investigated under BET analyzer to observe the particle surface area and UV-Vis analyzer to determine the band gap. The results demonstrated that the concentration of TBut/HCl ratio gave a very significant effect in transforming the mixing solution into geometrical shape of microspheres, nanoflowers and nanorods of titania as increasing the ratio. At TN0.5, the synthesized powder was clearly showing a circle geometrical shape of particles. The shape was suddenly changed into a round nanoflowers form consist of tiny nanorods at TN1. At TN1.5, the powder morphology shows the nanoflowers started to form in an irregular pattern. As the concentration ratio increased, the nanoflowers form disappeared and nanorods begin to clump. In addition, all synthesized powder was in rutile phases guided by XRD peaks and the band gap value reported from previous works. The particle surface area was also different for each sample since the geometrical shape of powder was changed by increasing the concentration (TBut/HCl) ratio. Thus, concentration ratio of the mixing composition plays a major role in transforming the overall morphologies and structures of hydrothermal synthesis titania particles.